Judicial Mafia in Criminal Justice System and Its Countermeasure - Anggun Paramarta (Universitas Ahmad Dahlan, 2018)
As a way of seeking justice, the judicial mafia is an outlaw action in the criminal justice process. Thus, it leads to judicial failure that damages the independence and impartiality of the court. That is because legal engineering carried out by judicial mafia syndicate violates the principles of due process of law in the criminal justice process. The current criminal justice process shows the blurring orientation of law enforcers in an effort to uphold the law and justice where the main purpose of litigation is not to uphold the law and justice, but to winning the cases. Therefore, it is necessary to overcome judicial mafia practices in the criminal justice system. The author uses normative juridical research method. The results of the study show that the cause of the flourishing judicial mafia in Indonesia’s criminal justice system is because law enforcement officers are not able to uphold their oaths of office. Therefore, overcoming judicial mafia practices can be done by penal or non-penal.